Analisis Kepatuhan Wajib Pajak Kendaraan Bermotor Dalam Upaya Meningkatkan Penerimaan Pajak Daerah Pada Kantor Samsat Padang Tahun 2016-2020 - Nini (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
This study will be used to determine the compliance of motorized vehicle taxpayers with Samsat Padang and to find out the inhibiting factors and drivers of vehicle tax compliance and the efforts made by Samsat to increase local tax revenues. The method used in this study is qualitative descriptive, with this method researchers can conduct direct interviews with the aim of knowing the compliance of motorized vehicle taxpayers at the Padang Samsat and also direct observations. The results of the study regarding the compliance of motorized vehicle taxpayers have been fairly obedient even the level of compliance of taxpayers at the Padang Samsat office has reached 95% of the total 395,625 taxpayers, this is supported by various driving factors that are being pursued by the Samsat so that taxpayers are always obedient and not violating obligations, there was only a decline in 2019-2020 due to Covid-19 which made the economy decline so that income was not fixed and it became difficult to make payments. The arrears of tax payable are only 5-10% percent rate. From the vehicle taxpayer compliance which has been very good, it can be seen that there is an increase in motor vehicle tax revenues that have exceeded the percentage target that has exceeded 100%. The increase in revenue also affects local tax revenues where from the results of the study that the contribution of motor vehicle taxes to local taxes reaches 70% as evidenced by the data obtained in 2016 the contribution reached 73%. This proves that the increase in motor vehicle tax revenues from efforts to maintain vehicle tax compliance ensures an increase in regional tax revenues.